Reducción de la pena en el delito de estupro, cuando el sujeto pasivo ejerce su derecho a tomar decisiones libres, informadas, voluntarias y responsables sobre su sexualidad - Gueledel Paucar, Paola Lizbeth (2019)
The present work of legal research is about: "Penalty reduction in the crime of statutory rape, when the victims exercises their right to take free, informed, voluntary and responsible decisions about his sexuality ", is oriented to the search for the establishment of a sanction that is proportional to the crime of statutory rape, in consideration that people who intervened during the execution of the sexual act have done so with their own will and in exercise of their right to sexual freedom. The statutory rape is a crime of a sexual nature, is stipulated in Article 167 of the COIP, its guiding verb is deception, indicating that the active subject deceives his victim, but like will demonstrate during the development of this work, persons within the ages of 14 and 18 cannot be seen as vulnerable people, who do not possess the ability to discern. It is wrong the idea that the statutory rape is considered as sexual deception toward a teenager, as a fact the Constitution of the Republic recognize the right to sexual freedom for all people, but the COIP is contradict with what is stipulated in relation to the crime of statutory rape, this would limit this right recognized in the Supreme Norm. Therefore, must be prepared a legal reform project to the COIP reducing the custodial sentence as a guarantee of the free exercise of the right of sexual freedom for both the passive subject and the active subject of the crime of statutory rape. The work realized in the theoretical field and the field investigation of this thesis, has allowed me to get opinions with clear and precise arguments, obtained from the literature review, implementation of surveys and interviews, which contributed to the verification of objectives and the proposed hypothesis, which reaffirms the proposed reform raised.